2018
DOI: 10.3390/ijms19102860
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PPARβ/δ in Melanoma Metastasis

Abstract: Background: Peroxisome proliferator–activated receptor (PPAR) β/δ, a ligand-activated transcription factor, is involved in diverse biological processes including cell proliferation, cell differentiation, inflammation and energy homeostasis. Besides its well-established roles in metabolic disorders, PPARβ/δ has been linked to carcinogenesis and was reported to inhibit melanoma cell proliferation, anchorage-dependent clonogenicity and ectopic xenograft tumorigenicity. However, PPARβ/δ’s role in tumour progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 46 publications
(53 reference statements)
4
21
0
Order By: Relevance
“…GW0742 decreased BrdU incorporation and the fraction of PCNA-positive cells significantly, GSK3787 had the opposite effects (Figure 1a-c). These findings are in line with the effects of PPARβ/δ modulation on the proliferation of melanoma cells reported by our group [5] and recently confirmed in a study where a PPARβ/δ antagonist enhanced melanoma progression [28]. To determine whether apoptosis might contribute to the observed effects on cell growth upon GW0742 treatment, we used Annexin V/propidium iodide (PI) labeling to detect apoptotic events followed by fluorescence-activated cell sorting (FACS) analysis.…”
Section: The Pparβ/δ Agonist Gw0742 Decreases Llc1 Lewis Lung Cancer supporting
confidence: 79%
“…GW0742 decreased BrdU incorporation and the fraction of PCNA-positive cells significantly, GSK3787 had the opposite effects (Figure 1a-c). These findings are in line with the effects of PPARβ/δ modulation on the proliferation of melanoma cells reported by our group [5] and recently confirmed in a study where a PPARβ/δ antagonist enhanced melanoma progression [28]. To determine whether apoptosis might contribute to the observed effects on cell growth upon GW0742 treatment, we used Annexin V/propidium iodide (PI) labeling to detect apoptotic events followed by fluorescence-activated cell sorting (FACS) analysis.…”
Section: The Pparβ/δ Agonist Gw0742 Decreases Llc1 Lewis Lung Cancer supporting
confidence: 79%
“…Moreover, because the melanoma cell line used for two of these studies was UACC903, which expresses mutant PTEN and an active AKT3, these results demonstrate that ligand activation and/or overexpression of PPARβ/δ are capable of preventing the negative effects of mutant PTEN and active AKT3, and possibly other mutations known to exist in this melanoma cell line . Consistent with these studies, genetic ablation and pharmacological inhibition of PPARβ/δ demonstrated that PPARβ/δ inhibited epithelial‐mesenchymal transition, migration, adhesion, and invasion of a mouse melanoma cell line and that PPARβ/δ prevented metastasis in a syngeneic mouse model of melanoma . By contrast, one published study suggests that ligand activation of PPARβ/δ with GW501516 promotes migration and invasion of a human melanoma cancer cell line .…”
Section: Pparβ/δ‐dependent Regulation Of Melanomasupporting
confidence: 66%
“…Reference(s) Activation of PPARβ/δ causes increased terminal differentiation [25][26][27][28] Activation of PPARβ/δ causes inhibition of proliferation [28][29][30][31][32][33][34][35][36] PPARβ/δ modulates bioactivation of chemical carcinogens 37 Ligand activation of PPARβ/δ inhibits non-melanoma skin cancer 32,33,[38][39][40] Inhibition of non-melanoma skin cancer by PPARβ/δ mediated by enhanced terminal differentiation 32,33,39 Inhibition of non-melanoma skin cancer by PPARβ/δ mediated by a block in the G2/M phase of cell cycle 36,40 Inhibition of non-melanoma skin cancer by PPARβ/δ mediated by enhanced senescence 41 Inhibition of non-melanoma skin cancer by PPARβ/δ mediated by inhibition of ER stress 42 Inhibition of non-melanoma skin cancer by PPARβ/δ influenced by inhibition of proinflammatory signaling [29][30][31]38 Ligand activation of PPARβ/δ inhibits melanoma [43][44][45][46] Abbreviations: ER, endoplasmic reticulum; PPARβ/δ, peroxisome proliferator-activated receptor-β/δ. PETERS ET AL.…”
Section: Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, FAs can bind and activate specific nuclear receptors, i.e., PPARs, thus controlling the expression of genes involved in lipid homeostasis, oxidative stress, and inflammation (59,60). Unfortunately, poor knowledge exists on this matter as the only evidence for a role of lipid signaling in melanoma biology comes from two recent papers in which the authors independently remarked an anti-tumor effect of PPARβ/δ and PPARγ in melanoma progression and metastasis (61,62).…”
Section: Metabolic Pathways In Melanomamentioning
confidence: 99%